Sociology of education - With a case study of social class and educational achievement in Trinidad - Osuji, Rose (Institute of Social and Economic Research, UWI, 1982)
This document is divided into two parts. Part I: The Theoretical and Empirical Background, examines the theoretical and empirical perspectives used in sociology of education. Part II: The Project, describes a project undertaken in Trinidad, in which the effects of some home variables--social class, attitude, achievement syndrome (values, motives, and aspirations), and some other variables--race and sex--singly and in combination, on educational attainment were examined
Keywords: Academic achievement